Marketing strategy for Android-based cowhide chips at the Suka Mandiri Business Group, Kendari City - Musram Abadi; La Ode Nafiu; Fitrianingsih Fitrianingsih; Andini Sulfitrana; Asma Bio Kimestri (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
The right cowhide chips marketing strategy during the COVID-19 pandemic is a marketing strategy with a digital or Android-based marketing concept which is considered to be able to provide benefits for the continuity and development of the Suka Mandiri business group as the target group for the Halu Oleo University Internal Community Service Program (PKMI-Internal). UHO). The objectives of implementing the PKM-I UHO program in 2020 are to introduce packaging and labeling techniques and to introduce Android-based marketing techniques to the Suka Mandiri group in the cowhide processing business. The method of implementing this program is counseling activities and technical guidance regarding Android-based marketing strategies for processed cowhide chips. The result of the implementation of this program is that the partner group understands the packaging and labeling techniques of cowhide chip products, digital, and marketing system by utilizing social media and marketplaces through Facebook and Instagram, and cowhide products produced by the Suka Mandiri business group as a local industry can be marketed in a fairly wide range.